Digital Education on Small Island: Maratua Island, Indonesia - Zaman, Muhammad Badrus; Nugroho, Setyo; Murdjito,; Djatmiko, Eko Budi; Busse, Wolfgang (International Journal of Marine Engineering Innovation and Research, 2025)
Indonesia has thousand islands to be developed. The total number of islands is 17,508. The potential that can be developed on a small island are environment, energy, transportation, education, information, and so on. In this study, focus is development of Maratua island, located in the district of Berau in East Kalimantan Indonesia. The potential of the island is development of marine tourism. In this case, Sustainable Island Development initiatives (SIDI) implemented to address the above challenges through multidisciplinary research activities. This research is starting from the transport sector, health, education, energy and implementation of information technology. In this context, the development of digital education is very important. This research provides solutions to the educational development of practical and suitable for the Maratua Island. This research develops the role of information and communication technology for teaching and learning activities island communities, examines the role of technology as a supplement teaching and learning process. In addition, this research also aims to design a physical architecture and digital education system that can be implemented in small islands in Indonesia, designing a learning method to support the teaching and learning process, and educating stakeholders about the concept of digital education.